Al-Farabi's Perspective on Happiness - Nurlaeli, Risa Anisa (Jurnal Sosial, Politik dan Budaya (SOSPOLBUD), 2023)
Al-Farabi is a philosopher who is famous for his very rational thinking. In this study, the method used is descriptive research with a qualitative approach. The data collection technique in this study is based on library research, namely the process of systematically identifying findings and analyzing documents containing information related to research problems. The results of this study explain that happiness is a thing or condition that although it is very difficult for everyone to achieve, they do their best to get it. If one succeeds in obtaining it, according to al-Fārābī, he has attained the perfection of life in the truest sense. Because the perfection that can be called al-sa'ādah, namely happiness, is the peak of happiness that is always attached to him.